Target Safety System design for the ESS target station - Sadeghzadeh, Atefeh; Olsson, Mikael; Coney, Linda (Journal of physics. Conference series, 2018)
The European Spallation Source (ESS) will be a 5 MW neutron spallation research facility where an energetic proton beam incident upon a helium-cooled tungsten target is converted to neutron beams. The liquid hydrogen moderator, water moderator, and reflector systems within the target monolith slow the high-energy spallation neutrons down to cold and thermal neutrons suitable for use by experiments. Several layers of control, protection, and safety systems will be implemented in order to ensure safe operation of this advanced facility. The Target Safety System (TSS) is part of the overall radiation safety plan for the Target Station. As such, in case of an abnormal event, the TSS will protect the public from exposure to unsafe levels of radiation, prevent the release of radioactive material beyond permissible limits, and bring the neutron spallation function into a safe state. This safe state is defined as no beam incident upon the target. Since the target is the source of the release of radiation in the presence of the beam, putting the target station into the safe state (no beam), brings the spallation process to the safe state. The TSS safety functions are based on the results from hazard and accident analyses done to evaluate radiation hazards within the target station. The most critical hazards are related to increased temperature of the target wheel tungsten, which can be the result of cooling system malfunctions or stopping of the rotating target. Therefore, the TSS will monitor parameters related to the cooling conditions and rotation of the target. As a safety system, the TSS is subject to requirements from the Swedish Nuclear Safety Authority (SSM), including single failure and common cause failure criteria. These requirements impact the system architecture in terms of redundancy, separation and diversity. Dedicated redundant and diverse TSS sensors are connected to two diverse and separated trains performing the same safety functions. Each train acts on diverse and separated mechanisms to stop the beam from reaching the target. This paper will describe the design and architecture of the TSS, which implements the safety functions identified in the radiation safety analyses and fulfils the SSM conditions.